Low Back Pain among Medical Students in Belgrade (Serbia): A Cross-Sectional Study - Isidora Vujcic; Nemanja Stojilovic; Eleonora Dubljanin; Nebojsa Ladjevic; Ivana Ladjevic; Sandra Sipetic-Grujicic (Pain Research and Management)
Aim. To examine the prevalence of low back pain, to identify self-perceived triggers of low back pain, and to investigate the impact of perceived pain on the daily activities and mood among medical students. Methods. This cross-sectional study enrolled 459 fourth year students at the Faculty of Medicine in Belgrade during December 2014. The anonymous questionnaire was used for data collection. In data analysis, the chi-square test and t-test were used. Results. The lifetime prevalence of low back pain was 75.8%, 12-month prevalence 59.5%, and point prevalence 17.2%. Chronic low back pain was experienced by 12.4% of the students. Both the lifetime (p=0.001) and the 12-month (p=0.001) low back pain prevalence rates were significantly higher among female medical students. Mental stress during an exam period (p=0.001), sitting at the university (p=0.002), fatigue (p=0.043), improper body posture (p=0.005), and lack of exercise (p=0.001) as self-perceived triggers of low back pain were significantly more often reported by female students, compared to males. Regarding daily functioning, the experience of low back pain mostly affects students sleeping (14.6%) and walking (12.0%). Conclusions. The prevalence of LBP is high among Belgrade medical students and significantly affects their everyday functioning.